Antecedent Factors of Organizational Performance in Manufacturing Firms - Yuswardi, Yuswardi; Farid, Ridhayati; Oktaviani, Debora (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2026)
This study examines the influence of work-life balance and training on organizational performance within manufacturing firms in Batam, Indonesia. With a focus on human resource dynamics, it highlights how these factors contribute to workplace harmony and employee engagement. A total of 365 employees participated in the research, utilizing a survey-based approach segmented into key areas such as leadership, recognition, work-life balance, training and development, organizational culture, and work engagement. Findings reveal that work-life balance and training significantly enhance employee engagement, which in turn positively affects organizational performance. Conversely, leadership and recognition did not show a direct impact on work engagement, suggesting that organizations must prioritize initiatives that foster work-life balance and invest in employee training for optimal outcomes. The study emphasizes the critical role of employee engagement as a mediator and suggests practical implications for manufacturing firms aiming to enhance their performance through improved human resource management strategies.